DIABESITY - 21st CENTURY THERAPEUTIC CHALLENGE - Nagendra Thota, Rohith; Puchchakayala, Goverdhan; Dornala, Sathya N. (International Journal of Ayurveda and Pharma Research, 2015)
The significant relationship between obesity and Type 2 Diabetes has been evidenced since ancient times. Ayurveda, Traditional Indian system of medicine, categorizes Prameha (diabetes) into two types i.e. Sthula prameha (diabetes in obese people) and Krisa prameha (diabetes in lean individuals). The alarming rise in prevalence of these disorders without any sign of decline in near future represents a global burden. Several prospective studies present impaired insulin release, impaired glucose tolerance, low grade inflammation and insulin resistance as the major factors for the development of type 2 diabetes. The low grade inflammation that dominates in obesity is the permanent elevation of plasma FFA and the predominant utilization of lipids by the muscle interfering with the uptake of glucose in skeletal muscle. This review article aims at understanding the potential mechanisms that lead human obesity to type 2 diabetes and therapeutic interventions for treating these disorders with a focus on the side effects of the conventional oral hypoglycemic agents and antiobesity agents. WHO and IDF moving with a goal for prevention of this global dual epidemic rather than curing by emphasizing the targets in various pathways and weight loss interventions. In this context, the review article highlights the potential targets for new therapeutic interventions and significance of weight loss for preventing and decreasing the progression of this multifactorial disorder.